2020
DOI: 10.3390/vaccines8040701
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Attitude and Communication in Early Settings: An Exploratory Study

Abstract: Background: This study assesses attitudes towards vaccination in mothers of new-born babies and explores its association with different exposures to communication. Methods: Data were collected through questionnaires administered by means of interviews. Results: Data highlighted that 20% of mothers showed an orientation towards vaccine hesitancy. As for the reasons behind the attitude to vaccine hesitancy, data showed that concern is a common feature. As for the different exposures to communication, 49% of moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…Similar findings from a recent study in Sudan [40] showed that pregnant women with low confidence towards vaccination were more likely to be involved in searching for additional vaccine information. Vaccination-related decisions of pregnant women in Italy were also found to be influenced by their exposure to information about vaccines [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings from a recent study in Sudan [40] showed that pregnant women with low confidence towards vaccination were more likely to be involved in searching for additional vaccine information. Vaccination-related decisions of pregnant women in Italy were also found to be influenced by their exposure to information about vaccines [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings underscore that lower vaccination coverage was more common among people with higher socioeconomic status in 10 upper-middle-income countries [16]. In LMICs, however, low uptake of childhood vaccination is associated with different determinants, including the behavioral and social factors of parents [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the only way to reach the minimum rate of vaccine uptake is to implement something like an informed consent procedure. In case of vaccination, parents, and especially mothers, are the first target as far as all the information about vaccine diffusion is concerned [ 32 , 33 , 34 ].…”
Section: Promoting Vaccination Through Informationmentioning
confidence: 99%
“…This sounded like replacing wrong elements with new information, rather than simply refuting incorrect beliefs. Although this communication strategy resembles psychological terrorism, it has been proven that similar strategies are effective in other campaigns of health promotion, for instance against smoking cigarettes and driving cars under the influence of alcohol [ 32 ].…”
Section: Promoting Vaccination Through Informationmentioning
confidence: 99%
“…The eradication of smallpox, the nearly global eradication of polio, and a substantial decrease within the morbidity and mortality related to other infectious diseases has been made possible with the evolution of vaccines. 1 Since 2013, the World Economic Forum has listed digital misinformation among the most threats to our society. WHO defines vaccine hesitancy as a "delay in acceptance or refusal of vaccines despite availability of vaccination services."…”
Section: Introductionmentioning
confidence: 99%